A CATREG model of destination choice for a mature Island destination - Almeida, António (2020)
This paper explores the factors that most strongly influence the attraction of tourists by mature island destinations during the stagnation phase of the resort lifecycle. Many such destinations have attempted to develop ex nihilo strategies, typically in the form of product differentiation. Others have adopted a strategy of consolidating their traditional tourism markets. It can be argued, however, that to undertake either strategy successfully requires a very clear understanding of the factors that determine tourists’ destination choices. The purpose of this paper is to identify the factors that shape tourists’ destination choices in the case of Madeira, a ‘classic’ destination in the Atlantic area that is in many ways typical of mature tourism destinations in their stagnation phase. The study presents the findings of a categorical regression (CATREG) based on a sample of 260 visitors. Insights are gained into how the destination can best be managed and marketed in order to facilitate the attraction and retention of tourists. The paper concludes that the most salient factors determining destination choice tend to be generic and cross-cutting, implying that destination management and marketing needs to be more focused on operational issues than it tends to be in many mature island destinations.